The Expression of Three Negative Co-Stimulatory B7 Family Molecules in Small Cell Lung Cancer and Their Effect on Prognosis - Qiu, Meng-jun; Xia, Qin; Chen, Yao-bing; Fang, Xie-fan; Li, Qiu-ting; Zhu, Li-sheng; Jiang, Xin; Xiong, Zhi-fan; Yang, Sheng-li (Frontiers in Oncology, 2021)
Background In recent years, immune checkpoint inhibitors have shown significant effects in a variety of solid tumors. However, due to the low incidence of small cell lung cancer (SCLC) and its unclear mechanism, immune checkpoints in SCLC have not been fully studied. Methods We evaluated the expression of PD-L1, B7-H3, and B7-H4 in 115 SCLC tissue specimens using immunohistochemistry. The clinical data of patients with SCLC were retrospectively reviewed to investigate three negative co-stimulatory B7 family molecules’ ability to affect the prognosis of SCLC. Results Among the SCLC patients with complete follow-up data (n = 107), sixty-nine (64.49%) expressed moderate to high B7-H3 levels, which correlated positively with tumor sizes (P < 0.001). Eighty (74.77%) patients expressed moderate to high B7-H4 levels, which correlated positively with metastases (P = 0.049). The positive expression of B7-H3 and B7-H4 correlated significantly with shortened overall survival (OS) (B7-H3, P = 0.006; B7-H4, P = 0.019). PD-L1 was positively expressed only in 13.08% of cancer tissues, and there was no significant correlation with prognosis. The Cox proportional hazards regression showed that B7-H3 was an independent prognostic indicator of OS (P = 0.028; HR = 2.125 [95% CI = 0.985-4.462]). Conclusions Our results suggest that B7-H3 has a negative predictive effect on SCLC. This outcome provides a theoretical basis for the subsequent research on immune checkpoint inhibitors targeting B7-H3.